1986
DOI: 10.1104/pp.82.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of Assimilate Uptake in Maturing Soybean Seeds

Abstract: ABSTRACIIn vitro assimilate uptake and metabolism were evaluated in embryos of known age isolated from seeds at mid-podfilling through physiological maturity. The capacity of isolated Wye soybean embryos to take up exogenous ['4Cjsucrose dropped nearly 4-fold in less than 1 week at incipient cotyledon yellowing. This drop in rate of sucrose uptake coincided with cessation of seed growth as well as rapid decline in leaf photosynthetic rate that preceded leaf yellowing. Conversely, the rate of j3Hjglutamine upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Furthermore, during seed maturation, a period not covered by the present study, soybean seed coats (Laszlo, 1990), as well as seed coats of other legumes (Hocking and Pate, 1977), show very pronounced accumulations of Ca2+. Because the embryo is still competent in dry matter uptake at this stage (VerNooy et al, 1986), this observation supports the hypothesis that the seed coat acts as a control site for CaZ+ transport. A similar conclusion was reached by Mix and Marschner (1976) in their study of P. vulgaris.…”
Section: Hypothesis: Seed Coat Moderates Mineral Transport To the Embryosupporting
confidence: 73%
“…Furthermore, during seed maturation, a period not covered by the present study, soybean seed coats (Laszlo, 1990), as well as seed coats of other legumes (Hocking and Pate, 1977), show very pronounced accumulations of Ca2+. Because the embryo is still competent in dry matter uptake at this stage (VerNooy et al, 1986), this observation supports the hypothesis that the seed coat acts as a control site for CaZ+ transport. A similar conclusion was reached by Mix and Marschner (1976) in their study of P. vulgaris.…”
Section: Hypothesis: Seed Coat Moderates Mineral Transport To the Embryosupporting
confidence: 73%
“…Although there were differences in the amount of green color remaining at physiological maturity depending on the growing conditions, there was no further increase in embryo dry weight after total loss of green color in embryo tissues. However, in one report, yellowed cotyledons were able to take up glutamine in vitro despite a sharp decline in sucrose uptake (19). Loss of green color from immature soybean embryos could be induced by slow drying (14) indicating that Chl degradation is enhanced by desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…Guldan and Brun (2) reported that rates of asparagine uptake into excised cotyledons of field grown soybean (Glycine max [L.] Merrill) were lowered when the tissue osmotic potential was reduced to -1.8 MPa and below. On the other hand, VerNooy et al (19) noted that excised yellowed cotyledon tissues from physiologically mature soybean embryos were able to take up glutamine but not sucrose. However, no measurements on tissue water relations were reported in the latter study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Translocation of sucrose from photosynthate into the embryo ceases when the seed coat changes from green to yellow and seed respiration declines rapidly (TeKrony et al, 1979). Likewise, cotyledons cease to take up sucrose when the cotyledon color changes from green to yellow (Vernooy et al, 1986). At this time, transport of water and nutrients into the seed ceases and the seed begins to shrink as it loses water.…”
Section: Accumulation Of Soluble Carbohydrates During Seed Developmentmentioning
confidence: 99%